Essential Oil Compositions and Antibacterial and Antioxidant Activities of Five Lavandula stoechas Cultivars Grown in Thailand. Issue 10 (19th September 2019) - Insawang, Suchawadee; Pripdeevech, Patcharee; Tanapichatsakul, Chutima; Khruengsai, Sarunpron; Monggoot, Sakon; Nakham, Thanawut; Artrod, Angkana; D'Souza, Priya E.; Panuwet, Parinya
Abstract: The essential oils of five Lavandula stoechas cultivars grown in Thailand were characterized for their volatile compounds using GC‐FID and GC/MS methods as well as screened for antibacterial and antioxidant activities. Dried aerial parts, including flowers and stems from each cultivar, were subjected to hydrodistillation for 4 h. The essential oil yields were 0.18 %–0.82 % w/w. Of the 95 compounds detected and identified, 1, 8‐cineole, fenchone, and camphor were considered the major compounds. Essential oil from each cultivar demonstrated different patterns of antibacterial activity and a variety of antioxidant properties. The highest antibacterial activity, MIC=0.39 mg mL −1, was observed from the essential oil of L. stoechas 'major' (against Klebsiella pneumoniae and Salmonella typhimurium ) and the essential oil of L. stoechas 'white lavender' (against S. typhimurium ). The essential oil of L. stoechas×viridis 'St. Brelade' possessed the highest antioxidant capacity, as determined by the DPPH and ABTS assays (IC50 of 67.65 and 89.26 mg mL −1, respectively). The results indicated that some of these essential oils could be used as key ingredients in lavender oil products in Thailand to increase their therapeutic efficacy, depending on their intended application. Abstract :